Congenital leptin deficiency and thyroid function - Paz-Filho, Gilberto (BioMed Central, 2009)
Thyroid function is closely related to leptin's secretion by the adipose tissue. In states of leptin-deficiency, the circadian rhythm of TSH is altered, leading to central hypothyroidism in animal models. In humans, central hypothyroidism has also been described in rare cases of congenital leptin deficiency. However, the thyroid phenotype in these cases is heterogeneous, with the occurrence of central hypothyroidism in a minority of cases. Here we describe thyroid function in four leptin-deficient humans (2 males aged 5 and 27, and 2 females aged 35 and 40), before and during leptin replacement with recombinant human methionyl leptin (r-metHuLeptin). The child was evaluated for four years, and the adults, for eight years. In addition, the adults were submitted to a brief withdrawal of leptin during six weeks in the sixth year. Our results show that, regardless of leptin replacement, our leptin-deficient patients have normal thyroid function. In spite of having an important role in regulating the hypothalamic-pituitary-thyroidal axis, leptin is not required for normal thyroid function. ClinicalTrials.gov Identifiers: NCT00659828 and NCT00657605